Neuroinflammation and neurodegeneration in diabetic retinopathy - Bianco, Lorenzo; Arrigo, Alessandro; Aragona, Emanuela; Antropoli, Alessio; Berni, Alessandro; Saladino, Andrea; Battaglia Parodi, Maurizio; Bandello, Francesco (Frontiers in Aging Neuroscience, 2022)
Diabetic retinopathy (DR) is the most common complication of diabetes and has been historically regarded as a microangiopathic disease. Now, the paradigm is shifting toward a more comprehensive view of diabetic retinal disease (DRD) as a tissue-specific neurovascular complication, in which persistently high glycemia causes not only microvascular damage and ischemia but also intraretinal inflammation and neuronal degeneration. Despite the increasing knowledge on the pathogenic pathways involved in DR, currently approved treatments are focused only on its late-stage vasculopathic complications, and a single molecular target, vascular endothelial growth factor (VEGF), has been extensively studied, leading to drug development and approval. In this review, we discuss the state of the art of research on neuroinflammation and neurodegeneration in diabetes, with a focus on pathophysiological studies on human subjects, in vivo imaging biomarkers, and clinical trials on novel therapeutic options.